Prognostic factors for overall survival in patients with metastatic castration-resistant prostate cancer treated with radium-223: a meta-analysis of real-world evidence - Song, Baolin; Shao, Huan; He, Yanmei; Zhu, Xinwei; Qin, Pengfei (Frontiers in Oncology, 2025)
BackgroundMetastatic castration-resistant prostate cancer (mCRPC) remains a lethal disease with limited treatment options. Radium-223 (Ra-223) improves survival in bone-predominant mCRPC, but real-world outcomes vary widely. This meta-analysis synthesizes real-world evidence to identify prognostic factors for overall survival (OS) in Ra-223-treated patients.MethodsFollowing PRISMA guidelines, we systematically searched PubMed, Embase, Web of Science, and Cochrane Library for observational studies reporting OS-associated prognostic factors in mCRPC patients receiving Ra-223. Pooled hazard ratios (HRs) were calculated. Study quality was assessed via Newcastle-Ottawa Scale.ResultsAmong 25 studies (n=8,795 patients), the pooled Ra-223 completion rate was 52.6% (95% CI: 48.9–56.3%). Each additional Ra-223 injection significantly improved OS (HR = 0.478, 95% CI: 0.362–0.630). Poorer OS correlated with older age (HR = 1.012/year), higher ECOG (HR = 2.078), elevated baseline PSA (HR = 1.922), ALP (HR = 1.981), LDH (HR = 1.702), NLR (HR = 2.255), and visceral metastases (HR = 2.342). Protective factors included hemoglobin levels (HR = 0.756/g/dL) and PSA/ALP declines during therapy (HR = 0.386 and 0.701, respectively). Prior chemotherapy predicted worse outcomes (HR = 1.425), while Gleason score and concurrent bone protectants showed no significant association.ConclusionReal-world data confirm Ra-223’s survival benefit is closely associated with treatment completion and baseline clinical factors. The findings support risk-stratified patient selection and tailored management in mCRPC.